Bianchi Type-I Cosmological Models for Biharmonic Particles and its Transformations in Spacetime - Korpinar, Talat; Turhan, Essin (Springer/Plenum Publishers, 2015)
In this article, we study timelike biharmonic particles in Bianchi type-I (B-I) cosmological model spacetime. We give a geometrical description of timelike biharmonic particle in spacetime. Moreover, we obtain transformations this particles. Some physical and geometric behaviour of these particles are also discussed in Bianchi type-I (B-I) cosmological model spacetime.
Keywords: Energy; Bienergy; Biharmonic particle; Bianchi type-I (B-I) cosmological model; Transformations